Simplified Chinese translation of 13 adult item banks from the Quality of Life in Neurological Disorders (Neuro-QoL) - Guanli Xie; Lidian Chen; Shanli Yang; Jing Tao; Chetwyn C. H. Chan; Allen W. Heinemann; David Cella; Jin-Shei Lai; Helena Correia; Alex W. K. Wong (BMC, 2018)
Abstract Background The Quality of Life in Neurological Disorders (Neuro-QoL) item banks evaluate and monitor the physical, mental, and social health of individuals with neurological conditions. Neuro-QoL items can be administered via short form or computerized adaptive testing. This paper describes the English-to-Simplified Chinese translation of 299 items from 13 adult item banks, which are publicly available. Methods Items were translated according to the Functional Assessment of Chronic Illness Therapy (FACIT) method, including forward and backward translation, reconciliation, expert reviews, and cognitive debriefing with both general and clinical populations in China. Results Most of the 299 Simplified Chinese items were well understood by the respondents. Revisions were made on a small number of items after cognitive debriefing. Although some difficulties were encountered in the translation process, all 13 item banks were linguistically validated with acceptable translations. Conclusion All Chinese adult Neuro-QoL measures are linguistically equivalent to their English sources. Future work includes psychometric validation of these measures in order to create a final version of the item banks. The translation methodology used in this study can serve as a blueprint for researchers in other countries interested in translating the Neuro-QoL.